An Entrepreneurial Ecosystems Approach to Encouraging Local Economic Development through a Village-Owned Enterprises Policy (A Case Study of Indonesian Village-Owned Enterprises (BUMDes)) - Purbasari, Ratih Purbasari; Soeling, Pantius Drahen; Wijaya, Chandra Wijaya (Archives of Business Research, 2019)
Local Economic Development (LED) can be used as a strategy in encouraging the acceleration of regional development. When combined with technological advancements, it presents its own challenges for the development of the local economy. LED focuses on local potential and existing resources, so it needs to identify the needs of local stakeholders and what they can do to ensure that their region reaches its potential in order to trigger the development process. The ability to identify and manage local potentials of the region requires entrepreneurial qualities and these can be gained through entrepreneurial ecosystems. One of the Indonesian government programs to encourage LED is BUMDes – a village-owned enterprise which is a collaboration between villagers and various parties to advance the local economy. This study aimed to find a mapping of the role of actors in the BUMDes Entrepreneurial Ecosystems (EE) to encouraging LED. The results showed that the actors involved in BUMDes EE have different roles in it. BUMDes management, as entrepreneurs, played a role in running the business optimally; Government was responsible for providing infrastructure, policy, and financial access; academicians supported knowledge transfer through research and community service programs; banking provided a link to funding and cash management training; the market had a role as the end customer and business customer; society provided support in shaping a culture that integrated entrepreneurship and was involved in BUMDes management. A constructive collaboration between all these roles in the entrepreneurial ecosystem enhanced the performance of BUMDes.